Allocation analysis of natural and cultivated grassland resources of eco-family pasture based on the theory of grassland agro-ecosystem discordance - FU Li; XIE Yingzhong; MA Hongbin; XING Ende; TIAN Xiumin (浙江大学学报. 农业与生命科学版, 2019)
In order to achieve sustainable development in pastoral areas, based on the theory of grassland agroe-cosystem discordance, we selected the meteorological factors in the study area of Otog Front Banner in recent 30 years and the water, soil, grass, and livestock in the area in recent years as the objects of study to discuss how to make a grassland resource allocation plan. The result showed that the natural environment in the study area was harsh and the annual precipitation was very limited; the groundwater resources were abundant but unevenly distributed, and the water consumption for agriculture and animal husbandry exceeded the expected limit. The proportion of natural grassland was obvious, but the overgrazing was serious, and the ecosystem was fragile, and the contradiction of herbage resources was prominent. The most important problem was time paradox, followed by space paradox, and finally by species paradox in the development of family ranches. Meanwhile, in the time paradox, it was necessary to reasonable matching cultivation of grassland resources according to the shortage period and surplus period of natural grassland; in the space paradox, on the one hand, developing high-yielding and high-quality cultivated grasslands to replace natural grassland functions in the towns of Aolezhaoqi and Chengchuan, and on the other hand, it was necessary to strictly control over the stock capacity of natural grassland, develop short-term fattening and improve turnover efficiency in the towns of Aangsu and Shanghaimiao.